2002
DOI: 10.1017/s0265021502000601
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for insertion of the laryngeal mask airway: comparisons between sevoflurane and propofol using fentanyl as a co-induction agent. A pilot study

Abstract: Although there was a faster induction with propofol-fentanyl, conditions for insertion of the laryngeal mask airway were similar in both groups. Haemodynamic stability was better with sevoflurane-fentanyl. The propofol-fentanyl combination was more cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…9 Ganatra SB et al and Rajiv Dwiwedi et al in their study found similar results and was comparable with present study. 10,11 Significant fall in MAP was noted in propofol group at baseline, 1 minute, 2 minutes, and 5 minutes after induction. Pulse rates were comparable in both groups in this study.…”
Section: Discussionmentioning
confidence: 94%
“…9 Ganatra SB et al and Rajiv Dwiwedi et al in their study found similar results and was comparable with present study. 10,11 Significant fall in MAP was noted in propofol group at baseline, 1 minute, 2 minutes, and 5 minutes after induction. Pulse rates were comparable in both groups in this study.…”
Section: Discussionmentioning
confidence: 94%
“…Ganatra et al 6 The intravenous low-dose Fentanyl-Midazolam combination seems to have dampened the haemodynamic response to LMA insertion. Pulse rate, systolic blood pressure and diastolic blood pressure revealed lower values in the group AII and BII, which were statistically significant when compared to group AI and BI respectively (p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that this time interval averaged around 135 sec with a SD of 40 sec. 3,4 We decided that a difference of 30 sec in insertion time would be deemed clinically significant. Sample size calculation, accepting alpha and beta errors of 0.05 and 0.2, respectively, suggested that 35 patients per group would be required.…”
Section: Methodsmentioning
confidence: 99%
“…Inhaled induction allows for maintenance of spontaneous ventilation, 1,2 which, in some patients, can facilitate airway management and help to preserve hemodynamic stability. 3 Despite such advantages, IIAS is generally lengthier than intravenous induction and can be less satisfactory for patients. [1][2][3][4] Several authors have studied the effect of adding a small dose of either a benzodiazepine or an opioid during IIAS and found that the pre-induction administration of sedative-hypnotics can accelerate induction, facilitate airway management, and increase patient satisfaction.…”
Section: Résumémentioning
confidence: 99%
See 1 more Smart Citation